GaSbBi Metal Semiconductor Metal Detectors for Mid-Infrared Sensing - Cao, Zhongming; Hulme, Sorcha; Veal, Tim D.; Ashwin, Mark J.; Sandall, Ian (Frontiers in Electronic Materials, 2022)
The viability of incorporating Bi and N into GaSb layers to realise photodetectors operating in the mid-infrared has been investigated. The effects of Bi and N on the cut-off wavelength of GaSb metal-semiconductor-metal photodetectors has been evaluated. The spectral responsivity measurements indicate a clear wavelength extension, to 1950 nm (Bi, 2.9%), 1990 nm (Bi, 3.8%), 2080 nm (Bi, 4.5%) and 2190 nm (N, 1.5%) from a reference GaSb device at 1720 nm, with only a relatively modest reduction in the external quantum efficiency (EQE). Comparisons of spectral response characteristics indicate that Bi incorporation reduces the carrier extraction and the impact of this on future device design is considered.